PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN KEAKTIFAN KETERAMPILAN BERBICARA DALAM MATA PELAJARAN BAHASA INDONESIA PADA SISWA KELAS IIIMI AL-MAWASIR PADANG KALUA - Islawati Islawati (IAIN Palopo, 2018)
This research reveals the application of picture and picture learning model by determining the subject matter which become the focus of the study, namely the activity on students' speaking skill. Thus, the purpose of this study to determine the ability of students 'speaking skills in the learning process using the media images in class III MI Al-Mawasir Padang Kalua'. The implementation of research using quantitative and qualitative approach. The type of research used is classroom action research (PTK) designed through three cycles. Each cycle lasts for two meetings. Subjects in this study were third grade students MI Al-Mawasir Padang Kalua, which amounted to 18 students consisting of 10 men and 8 women. Data collection techniques conducted in this study, namely interviews, tests, and observations. This research uses qualitative and quantitative data analysis techniques. Qualitative data was analyzed by qualitative descriptive analysis technique, ie categorization, data presentation, and data reduction, while quantitative data was analyzed by using percentage formula. The results of this study indicate that the average value of activity in students' speaking skills increases in each cycle. In the first cycle with a mean score of 68.05, it increases in cycle II with the average value of 71.52, and increasing again in cycle III with the average value of 84.72. Thus, it can be seen that the use of modelpicture and picture can effectively improve the students' speaking skills in the class IIIMI Al-Mawasir Padang Kalua.